Knowledge, attitudes and practices of nurses in infection prevention and control within a tertiary hospital in Zambia - Chitimwango, Priscilla Chisanga (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCur)--Stellenbosch University, 2017.